Analisis Kesulitan Peserta Didik dalam Memahami Materi Bahasa Arab - Anjani, Rina; Hafizah, Nurul; Hasanah, Fitrotul; Hidayat, Wahyu; Indriyana, Dina (UNIVERSITAS SERAMBI MEKKAH, 2025)
The aim of this research is to see how students face difficulties in understanding Arabic language material. This is because Arabic as the language of instruction in Islamic learning has different structures and rules from Indonesian, which often becomes an obstacle for students to understand the material. This research was conducted qualitatively through case studies and involved interviews and observations of a group of students studying at a secondary school. Understanding grammar (nahwu and sharaf), mastering vocabulary, and pronunciation and intonation that do not comply with the rules are the most frequently encountered problems, according to research results. Students' level of understanding is also influenced by motivational factors and failures in daily practice using Arabic. It is hoped that this research will provide information to educators.